2016
DOI: 10.1590/1414-431x20154738
|View full text |Cite
|
Sign up to set email alerts
|

Promoting inflammatory lymphangiogenesis by vascular endothelial growth factor-C (VEGF-C) aggravated intestinal inflammation in mice with experimental acute colitis

Abstract: Angiogenesis and lymphangiogenesis are thought to play a role in the pathogenesis of inflammatory bowel diseases (IBD). However, it is not understood if inflammatory lymphangiogenesis is a pathological consequence or a productive attempt to resolve the inflammation. This study investigated the effect of lymphangiogenesis on intestinal inflammation by overexpressing a lymphangiogenesis factor, vascular endothelial growth factor-C (VEGF-C), in a mouse model of acute colitis. Forty eight-week-old female C57BL/6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…did not promote disease resolution in mice with acute experimental colitis (18). Collectively, these results suggest either that lymphatic insufficiency may be causative of IBDs or that incorrect lymphatic expansion and function can exacerbate the disease phenotype.…”
Section: Introductionmentioning
confidence: 83%
“…did not promote disease resolution in mice with acute experimental colitis (18). Collectively, these results suggest either that lymphatic insufficiency may be causative of IBDs or that incorrect lymphatic expansion and function can exacerbate the disease phenotype.…”
Section: Introductionmentioning
confidence: 83%
“…11 and 36). Studies of IBD-affected intestine and experimentally inflamed colon have highlighted mesenteric and intestinal lymphatic abnormalities, including submucosal edema, lymphatic vessel dilation, lymphadenopathy, lymphatic obstruction, and lymphangiogenesis, the proliferation of new lymphatic vessels (2,3,6,7,15,31,32,50,70,71). Although these studies have mostly focused on intestinal lymphatic abnormalities, the role of the mesenteric lymphatics has more recently also been appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…The alteration of lymphatic drainage in humans has been observed through recently published dye injection studies, where dye was injected into resected regions of the gastrointestinal tract of IBD patients in areas with or without ulcers or inflammation [103]. These studies found that collecting lymphatics associated with creeping fat and that drain to the mesenteric LNs are remodeled by B cells and innate lymphoid cells invading the lymphatic wall, and that the lymphoid aggregates (also called tertiary lymphoid organs) alter Ag and immune cell trafficking to the mesenteric LN and thus contribute to disease progression [104]. In mouse models, there is not a clear consensus on how lymphangiogenesis affects IBD, and to what extent it is protective vs. pathological.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…In mouse models, there is not a clear consensus on how lymphangiogenesis affects IBD, and to what extent it is protective vs. pathological. In a mouse model of colitis induced by dextran sulfate sodium (DSS), Wang et al found that VEGF-C overexpression and associated increased lymphatic vessel density worsened the disease [104], which could be interpreted as lymphangiogenesis contributing to the pathogenesis of IBD. On the other hand, inflammatory lymphangiogenesis already occurs in DSS-induced colitis, and thus these experiments can only demonstrate that super(patho)physiological levels of VEGF-C, in excess of what is produced in the inflamed environment, exacerbates inflammation and tissue damage resulting from DSS.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%